2018
DOI: 10.1007/s00705-017-3697-2
|View full text |Cite
|
Sign up to set email alerts
|

HPV genotypes detected by linear array and next-generation sequencing in anal samples from HIV positive men who have sex with men in Mexico

Abstract: The incidence of anal cancer has been rising, especially in HIV+ patients and has been associated with HPV infection. HIV+ patients are more at risk of HPV coinfection and are seven times more likely to have persistent HPV infection; moreover, HIV+ men have an increased risk of developing anal cancer compared to HIV+ women. The development of screening strategies for the detection of HPV in HIV+ men is of major importance; however, there is not enough information about the HPV genotypes and variants that are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
3
1
Order By: Relevance
“…Other HPV types with higher prevalence in general were HPV 18 followed by HPV 52, 35, 39 and 45. In contrast, a study that detected HPVs using 454 NGS and reported results based on the total number of HPV reads in anal specimens of HIV+ MSM in Mexico, documented that HPV 45 was the most prevalent followed by HPV 51, 58, 16, 52 and 59 . That study and ours identified most of the known LR‐HPVs and the following HPV genotypes that are not classified as HR or LR; HPV 44, 32, 74, 85, 86, 102 and 97.…”
Section: Discussioncontrasting
confidence: 54%
“…Other HPV types with higher prevalence in general were HPV 18 followed by HPV 52, 35, 39 and 45. In contrast, a study that detected HPVs using 454 NGS and reported results based on the total number of HPV reads in anal specimens of HIV+ MSM in Mexico, documented that HPV 45 was the most prevalent followed by HPV 51, 58, 16, 52 and 59 . That study and ours identified most of the known LR‐HPVs and the following HPV genotypes that are not classified as HR or LR; HPV 44, 32, 74, 85, 86, 102 and 97.…”
Section: Discussioncontrasting
confidence: 54%
“…Interestingly, in our study, the most frequent HR-HPV genotype in all men was HPV33 (33.3%), contrary to the abovementioned studies reporting low frequencies for this genotype (5–7%) [ 15 , 17 , 18 ]. In another study from Mexico using linear array, the most frequent genotypes were HPV62 and HPV81 [ 23 ]. In our study, these genotypes were not intentionally sought out, because they were not included in the employed method [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…As in previous studies, in the present series HPV16 was positive in about 60% of the HSIL/AIN2-3 lesions and HPV18 was found in 7.5% of the HSIL/AIN2-3 samples. [36,37]. It has been shown that the percentage of HPV16 and 18 genotypes increases with the severity of the diseases, and it is particularly high in invasive cancers [38].…”
Section: Discussionmentioning
confidence: 99%